2003
DOI: 10.1021/bi034277y
|View full text |Cite
|
Sign up to set email alerts
|

The Prohormone Processing Enzyme PC3 Is a Lipid Raft-Associated Transmembrane Protein

Abstract: The biosynthesis of most biologically active peptides involves the action of prohomone convertases, including PC3 (also known as PC1), that catalyze limited proteolysis of precursor proteins. Proteolysis of prohormones occurs mainly in the granules of the regulated secretory pathway. It has been proposed that the targeting of these processing enzymes to secretory granules involves their association with lipid rafts in granule membranes. We now provide evidence for the interaction of the 86 and 64 kDa forms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 47 publications
3
48
1
Order By: Relevance
“…Anti-CgA polyclonal IgG was previously described (Arnaoutova et al, 2003). Anti-p115 mouse IgG is from BD Transduction Laboratories (San Jose, CA).…”
Section: Antibodiesmentioning
confidence: 99%
“…Anti-CgA polyclonal IgG was previously described (Arnaoutova et al, 2003). Anti-p115 mouse IgG is from BD Transduction Laboratories (San Jose, CA).…”
Section: Antibodiesmentioning
confidence: 99%
“…The presence of full-length PC1/3 with its C-terminal region intact is required for the processing of prorenin to renin in granules in AtT-20 cells (Jutras et al 1997). Without its lipid-binding C-terminal region (Jutras et al 2000, Arnaoutova et al 2003, PC1/3 is not sorted to the regulated secretory pathway, and renin is secreted constitutively. PC2 also contains an alpha-helical, lipid-binding C-terminal tail that directs it to the regulated pathway (Assadi et al 2004), thus enabling it to act as a membrane-bound receptor/ tether.…”
Section: Introductionmentioning
confidence: 99%
“…Sequence similarity suggests that GLP-2 is also an alpha-helix, and it has been suggested that the structure of the entire proglucagon molecule may form a 'trimer' of alpha helices (Dey et al 2004). Conserved alpha-helix structures within the amino-terminal end of prosomatostatin (Mouchantaf et al 2001) and the C-terminal ends of PC1/3 (Jutras et al 2000, Arnaoutova et al 2003, PC2 (Assadi et al 2004), PC5/6a ) and CPE (Dhanvantari et al 2003a are critical in targeting these proteins to secretory granules. Additionally, the sequence of glucagon contains an internal pair of basic amino acids, Arg17Arg18, which does not serve as a PC1/3 or PC2 cleavage site (Bataille 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These include paired basic residues that may interact with granule-resident PC enzymes (14, 24 -26), N-terminal disulfide-bound loops (27,28), and other domains that mediate sorting by binding to caboxypeptidase E (2), calcium-binding domains that lead to aggregation (reviewed in Ref. 8), and ␣-helices that either traverse or interact with membranes (3,(5)(6)(7). Finally, proteins may contain more than one single type of sorting domain so that analyses in which any one of these is eradicated will not eliminate sorting in the context of the native protein.…”
Section: Discussionmentioning
confidence: 99%
“…This process, called regulated secretion, depends on a highly selective triage of proteins within or just after the TGN. Retention in dense core secretory granules is not a random process and granulesorted proteins must possess unique properties or must interact with other cellular components in a unique way to end up in this organelle (1)(2)(3)(4)(5)(6)(7).…”
mentioning
confidence: 99%